KORELASI MINAT BACA DAN MOTIVASI DENGAN HASIL BELAJAR TEMATIK SISWA KELAS IV SEKOLAH DASAR - Wahyuningsih, Tri; Kartono, Kartono; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to describe the correlation between reading interest and learning motivation with student learning outcomes in the thematic learning of grade IV SDN 36 in South Pontianak. The method used is descriptive method in the form of research studies of relationship (interrelation studies) by using correlation studies. This study is a population study with a total of 47 student. Data collection.tools used were questionnaires and document of leaurning outcomes. The result showed that students interest in learning at SDN 36 in South Pontianak was 72,92% included in the category of â€œenoughâ€ and students learning motivation was 77,37% in te â€œgoodâ€ category. While the learning outcomes of SDN 36 in South Pontianak students obtained an average of 84,08. Based on the results of statistical calculations using the multiple correlation formula for calculation of reading interest and learning motivation with student learning outcomes obtained r ccount of 0,242, while the r table of 0,288 means r count < r table or 0,242 < 0,288. Based on the results of study, the relationship between interest in reading and learning motivation with student learning outcomes in thematic learning grade IV State Elementary School 36 South Pontianak included in the low categoryKeywords: Learning Motivation, Learning Outcomes, Reading Interest, Thematic